The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.cpr.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

A lifetime approach to major depressive disorder: The contributions of psychological interventions in preventing relapse and recurrence

Abstract: Major depressive disorder (MDD) is highly disabling and typically runs a recurrent course. Knowledge about prevention of relapse and recurrence is crucial to the long-term welfare of people who suffer from this disorder. This article provides an overview of the current evidence for the prevention of relapse and recurrence using psychological interventions. We first describe a conceptual framework to preventive interventions based on: acute treatment; continuation treatment, or; prevention strategies for patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
237
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(254 citation statements)
references
References 101 publications
(171 reference statements)
14
237
0
3
Order By: Relevance
“…103 The distinction between continuation and maintenance phases was based on a theoretical difference between relapse (symptoms recurring before resolution of the current episode) and recurrence (symptoms that constitute a new episode, after recovery from the previous episode). 103 Recent reviews have highlighted the inconsistent use of these terms and lack of evidence to support distinct demarcations between episodes 104 ; hence, CANMAT continues to endorse a single concept of relapse/recurrence and the 2 treatment phases ( Table 9). …”
Section: What Are the Phases Of Treatment?mentioning
confidence: 99%
See 1 more Smart Citation
“…103 The distinction between continuation and maintenance phases was based on a theoretical difference between relapse (symptoms recurring before resolution of the current episode) and recurrence (symptoms that constitute a new episode, after recovery from the previous episode). 103 Recent reviews have highlighted the inconsistent use of these terms and lack of evidence to support distinct demarcations between episodes 104 ; hence, CANMAT continues to endorse a single concept of relapse/recurrence and the 2 treatment phases ( Table 9). …”
Section: What Are the Phases Of Treatment?mentioning
confidence: 99%
“…Table 10 shows the risk factors for recurrence. 104,108 Risk-prediction support tools have been developed to estimate risk of recurrence based on individuals' unique exposure to a key set of risk factors. 109 While risk-prediction Table 11 lists some examples of e-Mental health resources that are evidence-based and/or come from credible sources.…”
Section: Who Needs Longer Term Treatment?mentioning
confidence: 99%
“…Time-limited continuation and maintenance phase psychotherapies also appear promising for relapse prevention [16,17,18,19,20,21,22,23,24]. Specifically, continuation cognitive therapy and continuation phase fluoxetine were shown to reduce relapse over 8 months significantly more than a pill placebo in adults who responded to acute-phase cognitive therapy and had an elevated risk of relapse due to slow or incomplete remission in acute-phase cognitive therapy.…”
mentioning
confidence: 99%
“…Vitriol et al (16), having commonly found traumatic experiences in the history of depressive patients, pointed out the necessity to complement pharmacotherapy with interventions directed at the trauma in order to improve the patients' state. Bockting et al (17) showed that mental trauma is a predisposing factor for repeated and resistant depression. Our contribution also shows the importance of investigating traumatic experiences in depressive patients.…”
Section: Discussionmentioning
confidence: 99%